Current state and influencing factors of social alienation in patients with stress urinary incontinence - Ting Chen; Xiaodan Li; Lei Liu; Xiaoting Wei; Sen Li; Jingjing Gong; Lili Xing; Lianhua Bai (Gynecology and Obstetrics Clinical Medicine)
Objective To understand the current level of social alienation among patients with stress urinary incontinence (SUI) and analyse the influencing factors to provide a foundation for better clinical support for patients’ reintegration into society.Methods We conducted a comprehensive survey and analysis involving 230 patients with SUI using a general information questionnaire, a general sense of alienation scale and a social impact scale.Results The general sense of alienation scale score of patients with SUI was 25.43±13.994, while the social impact score was 39.25±12.167. Multiple linear regression analysis revealed that marital status, primary caregiver, presence of concurrent illnesses and severity of urinary incontinence were the key influencing factors contributing to SUI-related social alienation (p<0.05).Conclusion Patients who suffered from SUI experienced a moderate level of social alienation. Tailored interventions are recommended, especially for individuals who are divorced, rely on friends or relatives as primary caregivers, have concurrent illnesses or experience severe SUI, to enhance their social integration.